Methods to Promote Green Marketing in India: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Green marketing refers to the process of selling products andor services based on their environmental benefits. Such a product or service may be environmentally friendly in itself or produced in an environmentally friendly way.The obvious assumption of green marketing is that potential consumers will view a product or service's greenness as a benefit and base their buying decision accordingly. The not-so-obvious assumption is that consumers will be willing to pay more for green products than they would for a less-green comparable alternative product.While green marketing is growing greatly as increasing numbers of consumers are willing to back their environmental consciousnesses with their dollars, it can be dangerous. The public tends to be skeptical of green claims to begin with and companies can seriously damage their brands and their sales if a green claim is discovered to be false or contradicted by a company's other products or practices.